A founding father of neuroscience: Floyd E. Bloom, 1936–2025 - Gary Aston-Jones; Stephen L. Foote; John H. Morrison (Proceedings of the National Academy of Sciences, 2025)
Floyd E. Bloom, M.D. was a prominent leader and spokesperson for the neuroscience and broader scientific communities; sadly, Floyd passed away on January 8, 2025. His scientific contributions were focused on multidisciplinary characterizations of transmitter-specific neural pathways in the brain. An innovative neuroanatomist and neurophysiologist, he spearheaded the development of new techniques and multidisciplinary paradigms for demonstrating the functions of neurotransmitters at the circuit, cellular, and subcellular levels. His work was especially important for mapping monoaminergic and peptidergic pathways and describing their physiologic and behavioral roles. He played a seminal role in developing the field of modern neuropharmacology at all levels, from the molecular to the behavioral.